On the Greek-philosophical impact on Labeo’s definition of the locatio conductio operis (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
Roman law was influenced by Hellenistic concepts across the various periods of its development. This influence is reflected in the inclusion of Greek terms in the Latin texts of Roman jurists. The following article addresses Labeoʼs definition of locatio conductio operis and its interpretation in Romanist doctrine. The article explores Labeo’s use of the terms ἀποτέλεσμα and ἔργον in his definition, offering a linguistic analysis of these lines that attends to the meaning of the Greek language usage. In conclusion, the significance of the Hellenistic influence here is grounded by reviewing some relevant aspects of Greek law and the circumstances under which Labeo wrote his text, which is cited in D. 50.16.5.1.
Keywords: Roman law; Greco-Hellenistic law; locatio conductio operis; apotelesma; ergon; Labeo; Aristotile